Identification of spatial and temporal land cover alterations in the Jakarta TOD areas utilizing Google Earth data - Tanuda Pedro Rusdiono; Adi Wibowo (Regional Development Information Center, Universitas Sebelas Maret, 2025)
The Provincial Government of Special Capital Region of DKI Jakarta has designated Transit Oriented Development (TOD) areas at several Mass Rapid Transit (MRT) station locations through Regional Regulation Number 31 of 2022 concerning the Detailed Spatial Planning (RDTR) of DKI Jakarta. This designation aims to enhance spatial utilization within these areas. However, there are concerns that the intensified spatial use may not fully adhere to the minimum planning criteria stipulated in the regulation. This study aimed to identify land-cover changes in Jakarta’s TOD areas between 2012 and 2024. Although the official TOD implementation commenced in 2022, the selection of 2012 as a baseline provides insight into historical land cover conditions before significant TOD influence, thereby allowing an assessment of long-term trends. Satellite imagery from Google Earth for the years 2012 and 2024 were analysed using GIS tools and manually digitized classifications, with a Sankey diagram used to visually represent land cover transitions, particularly in the Lebak Bulus area. The findings revealed that while most TOD areas show limited changes, Lebak Bulus experienced significant conversion of vegetation and open spaces into built-up areas.